Ideological Uniformity and Political Integralism in Europe and Indonesia: A Kuyperian Critique - Un, Antonius Steven (Philosophia reformata, 2022)
This article presents a Kuyperian critique of ideological uniformity and political integralism in Europe and Indonesia. The background of Kuyper’s articulation of the principle of sphere sovereignty was his struggle with the liberals, the French Revolution, and the German idea and application of state sovereignty. Kuyper struggled with the liberals because he rejected ideological uniformity. He struggled with the ideals of the French Revolution because he rejected popular sovereignty and, later on, political integralism. Kuyper’s rejection of ideological uniformity and political integralism resulted in the articulation of the principle of sphere sovereignty. Such uniformity and integralism also characterized Suharto’s leadership in twentieth-century Indonesia, especially his doctrine of Pancasila as the only basis for the state and civil society and his ideology of the integralist state of Indonesia. I criticize those doctrines from the perspective of Kuyper’s principle of sphere sovereignty.